Preparation and diagnostic medicinal substance for regulating the thyroid gland (Baghdad Science Journal, 2025)
Research included the preparation of medicinal substances ( propyl thiouracil). Which is the rule thiourea and related compounds a fundamental rule in preparation fall within the range of drugs of anti-thyroid activity (Antithyroid Drug ) , this drug prevents the thyroid hormone production against excessive activity of the thyroid gland .That the formation of iodine is important for their impact on hormone secretion thyroid , the two types, thyroxin or T4 is the main hormone ,Triiodothyronine or T3, and these hormones released by hormone regulator called (TSH) . Article attend thiourea treatment with an alcohol- soluble sodium and added to the interaction rule b- oxo ester after adjusting the PH=4 output ( propylthiouracil )the melting point (219-222oC). Determination material producet by (UV.Vis) Spectrometer at 272nm , as well as infrared spectrometer ( I.R.Spectra ) were determined purity of material by HPLC and their conformity with pharmacopoeia USP(24) given article the validity of the medicinal use the drug control and acquired with surgery or without surgery at a dose (100mg) three times a day and usually the dose should not exceed the limits (50-150mg)a day.